Influence of Double-Panel Structure Modification on Vibroacoustical Properties of a Rigid Device Casing - Anna CHRAPOŃSKA; Jarosław RZEPECKI; Krzysztof MAZUR; Stanisław WRONA; Marek PAWEŁCZYK (Archives of Acoustics, 2020)
Nowadays, noise generated by devices is a serious issue in industry and in everyday life, because it may cause health damage to humans. In this research, a cubic rigid device casing built of double-panel thin steel walls is employed to reduce noise emitted from an enclosed noise source. Double-panel structure is used because of good sound insulation it provides. There exist three main groups of noise reduction methods, i.e. passive, semi-active and active. In this paper, a semi-active modification of double-panel structure is applied and examined. The bistable actuator (solenoid) mounted between incident and radiating plates changes its state due to applied constant voltage, causing the coupling of plates. Experimentally measured natural frequencies and modeshapes of the structure are compared to the simulation results. The influence of proposed modification on dynamical properties of the structure is analyzed and discussed.